Arch combined material water storage module - LI XIHONG; MA JIA; LIU YIN; MA NI (2016)
The utility model provides an arch combined material water storage module, including water storage unit and joint in the end cover at its both ends, the water storage unit is both ends and bottom surface open -ended domes, and the water storage unit is inside to be formed along the water storage passageway of its axial setting, be provided with the connecting tube that is used for connecting outside rainwater pipeline on the end cover, connecting tube and water storage passageway are linked together. The utility model discloses effectively solve the clearance of square plastic module and safeguard that difficulty, space utilization hang down, bear the weight of low scheduling problem. 本实用新型提供了种拱形复合材料储水模块，包括储水单元和卡接于其两端的端盖，储水单元为两端和底面开口的拱形结构，储水单元内部形成沿其轴向设置的储水通道；端盖上设置有用于连接外部雨水管道的连接管道，连接管道和储水通道相连通。本实用新型有效解决方形塑料模块清理维护困难、空间利用率低、承载低等问题。